Desenvolvimento de membranas com capacidade de liberação controlada de fármacos a partir de materiais orgânico-inorgânicos para implantodontia - Oshiro Junior, João Augusto [UNESP] (2014)
Among the membranes used for guided bone regeneration the resorbable membranes stand out for do not need the second surgery, a fact that can cause tissue damage beyond uncomfortable that the second surgery itself provides the patient.However, there is no on the market a membrane considered appropriate. The objective of this study was to develop a membrane from hybrid materials ureasil polyether for guided bone regeneration, able to isolate the bone graft and simultaneously drug release controlled or protein, resulting in a membrane capable of improving the physiological response of the tissue bone decreasing the bone formation. The materials used were synthesized from solgel method using polymers poly ethylene oxide (POE) and poly propylene oxide (POP) of different molecular weights (400, 1900, 2000 g mol-1).The drug used as model was dexamethasone acetate. The results of swelling in the presence of artificial saliva showed that with the increase in the proportion of ureasilPOP2000 and ureasil POE1900 in the mixture occurred an increasing mass, but this increase is more significant for mixture with the ureasil-POE1900.The evolution of SAXS curves during the release experiment with artificial saliva reveals that the mixture formed by ureasil-POP400/POE1900 leads to displacement of the correlation peak for low values of q and the increase in the intensity of the peak but the reason hydrophobic in the mix ureasilPOP400/POP2000 this displacement for low values of q is invariable. The release test showed that it is possible to control the release rate of the drug from the variation of the mixtures and ureasil-POP400/POP2000 ureasilPOP400/POE1900. Results of the microtomography showed that bone defects containing the ureasil-polyether membranes tested showed bone growth statistically similar to bone defects containing commercial collagen membrane (Bio-Gide, Geistlich Pharma).